Detection and molecular characterization of Actinomyces denticolens causing lymph node abscessation in horses - van den Wollenberg, L.; van Maanen, C.; Buter, R.; Janszen, P.; Rey, F.; van Engelen, E. (Frontiers in Veterinary Science, 2023)
Introduction Abscessation of equine head lymph nodes can be caused by various bacteria, but Streptococcus equi subsp. equi is mainly involved. At our laboratory, samples of three unrelated horses with submandibular abscesses were found negative for S. equi, and further testing proved the presence of another genus. This raised the question for the exact identity of this pathogen and whether these isolates were epidemiologically related and it warranted further characterization with regards of virulence and resistance factors. Methods Culture followed by identification using MALDI-TOF MS, MIC testing and whole genome sequencing (WGS) was performed to characterize the bacteria. Results Bacterial culture and subsequent identification with MALDI-TOF MS resulted in the reliable identification of A. denticolens in two of the three cases. Final confirmation of A. denticolens for all three isolates was achieved by analysis of the WGS data, supported by multilocus sequence typing (MLST). The three isolates showed 95% nucleotide sequence identity. The number of single nucleotide polymorphisms (10,170 to 36,058) indicated that the isolates were not clonal, suggesting that these cases were epidemiologically unrelated. Only four known virulence related genes were detected. The absence of known antibiotic resistance genes was in line with the high susceptibility, as indicated by the susceptibility patterns obtained for two of the three isolates. Conclusion We conclude that A. denticolens should be included in the differential diagnosis of (submandibular) lymph node abscessation in horses, especially if strangles cannot be confirmed with laboratory diagnostics. Furthermore, we report the first draft genome of A. denticolens isolated from horses.